Dislocated distal radial fractures in adult patients: 4 weeks versus 6 weeks of cast immobilisation following reduction, a multicentre randomised controlled trial, study protocol. Issue 3 (15th March 2019) - van Delft, Eva A K; Bloemers, Frank W; Sosef, Nico L; Bonjer, H J; Schep, Niels W L; Vermeulen, Jefrey
Abstract : Introduction: Up to 30% of patients with a dislocated distal radial fracture (DRF) treated with closed reduction and cast immobilisation suffer from long-term functional restrictions. It remains unclear, whether duration of cast immobilisation influences functional outcome. The aim of this study is to evaluate whether the functional outcome of dislocated DRFs could be improved by shortening the period of immobilisation. Methods and analysis: A single blinded multicentre randomised controlled trial is initiated. Four weeks of plaster cast immobilisation is compared with six week plaster cast immobilisation in adult patients with adequate reduced DRFs. Primary outcome parameters are functional outcome measured with the Patient Rated Wrist Evaluation after 1 year of follow-up (FU). Secondary outcomes are: Disability of Arm, Shoulder and Hand Score after 1 year, 36-Item Short Form Health Survey after 1 year, functional outcome earlier in FU (6 weeks, 12 weeks and 6 months), range of motion, pain level and complications: number of re-interventions, secondary dislocation, delayed and non-union. Ethics and dissemination: The medical ethical committee VUmc approved the study protocol (2018.004, NL62861.029.17). The expectation of this study is that a shorter duration of plaster cast immobilisation is beneficial. This risk of specific complications is low and generally similar in both treatment options. FU is standardised according to current trauma guidelines. Present literature indicates that both treatment options that are used within this study are accepted protocols for treatment of dislocated DRFs. This trial will provide Level-I evidence for the comparison of functional outcome between the two treatment options for dislocated DRFs. Results of this study are expected to be published as a prospective, multicentre, randomised controlled trial article in 2021. Trial registration: The Netherlands National Trial Register: NTR 6600, ABR: NL62861.029.17. Medical Ethical Committee VUmc registration number: 2018.004.